Progress in gene therapy treatments for prostate cancer. (25th May 2021) - Xue, Jingxin; Chen, Keming; Hu, Heyi; Gopinath, Subash C.B.
Abstract: Prostate cancer is one of the predominant cancers affecting men and has been widely reported. In the past, various therapies and drugs have been proposed to treat prostate cancer. Among these treatments, gene therapy has been considered to be an optimal and widely applicable treatment. Furthermore, due to the increased specificity of gene sequence complementation, the targeted delivery of complementary gene sequences may represent a useful treatment in certain instances. Various gene therapies, including tumor‐suppressor gene therapy, suicide gene therapy, immunomodulation gene therapy and anti‐oncogene therapies, have been established to treat a wide range of diseases, such as cardiac disease, cystic fibrosis, HIV/AIDS, diabetes, hemophilia, and cancers. To this end, several gene therapy clinical trials at various phases are underway. This overview describes the developments and progress in gene therapy, with a special focus being placed on prostate cancer.